2008
DOI: 10.1016/j.molonc.2008.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging and cancer: A review

Abstract: Multiple biomedical imaging techniques are used in all phases of cancer management. Imaging forms an essential part of cancer clinical protocols and is able to furnish morphological, structural, metabolic and functional information. Integration with other diagnostic tools such as in vitro tissue and fluids analysis assists in clinical decision-making. Hybrid imaging techniques are able to supply complementary information for improved staging and therapy planning. Image guided and targeted minimally invasive th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
488
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 672 publications
(494 citation statements)
references
References 381 publications
2
488
0
4
Order By: Relevance
“…There is a growing awareness that assessment of location, magnitude and duration of transgene expression in vivo through various modern noninvasive imaging technologies may help develop efficient and safe gene therapy protocols. 3,4 Currently, the three most promising suicide gene/prodrug combinations are (1) herpes simplex virus thymidine kinase (HSV1-tk) with ganciclovir (GCV), 5 (2) CD (cytosine deaminase) from bacteria or yeast with 5-fluorocytidine 6,7 and (3) bacterial nitroreductase (NTR) with CB1954. 8 Of the three, HSV1-tk/GCV is at the forefront of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing awareness that assessment of location, magnitude and duration of transgene expression in vivo through various modern noninvasive imaging technologies may help develop efficient and safe gene therapy protocols. 3,4 Currently, the three most promising suicide gene/prodrug combinations are (1) herpes simplex virus thymidine kinase (HSV1-tk) with ganciclovir (GCV), 5 (2) CD (cytosine deaminase) from bacteria or yeast with 5-fluorocytidine 6,7 and (3) bacterial nitroreductase (NTR) with CB1954. 8 Of the three, HSV1-tk/GCV is at the forefront of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Data from this study had shown after years of development in breast imaging, women perception of pain during mammography still remain (Asghari and Nicholas, 2004;Keemers-Gels et al, 2000). Existence of a new imaging tool with much lesser pain may be the answer to boost up the popularity for breast health screening among women worldwide (Fass, 2008).…”
Section: Discussionmentioning
confidence: 86%
“…Ultrasound is one of the imaging methods employed by many people all over the world to identify a mass of tissue in the ovarian, breast, kidney, liver, prostate, pancreatic and uterine [8].…”
Section: Preliminaries Ultrasound Imagingmentioning
confidence: 99%
“…Therefore, there is more heat and finally more expansion in tumor tissue in compare with healthy tissue around it [11]. Photoacoustic tomography and photo-acoustic microscopy are two type of Photo-acoustic image [8,12,13]. The steps toward photoacoustic imaging of the targeted area are illustrated in Figure 5.…”
Section: Photo-acoustic Imagingmentioning
confidence: 99%